Mineral Pitch Attenuates Oxidative Stress-Induced Eryptosis in Human Erythrocytes via Antioxidants and Calcium-Modulatory Mechanism - Hassan, Muhammad Najamul; Rasheed, Muhammad; Butt, Namra; Anwar, Nida; Shahab, Ahmad; Ashiq, Maryam; Ali, Wazir Hamid; Jilani, Kashif (Indus Journal of Bioscience Research, 2025)
Background: Erythrocytes are highly susceptible to oxidative stress, which can induce eryptosis programmed cell death mechanism characterized by hemolysis, membrane blebbing, and cell shrinkage. Mineral Pitch (Asphaltum punjabium), a traditional medicinal substance, has demonstrated antioxidant potential, but its effect on erythrocyte integrity under oxidative stress has not been thoroughly investigated. Objective: This study aimed to evaluate the antioxidant and cytoprotective effects of Mineral Pitch on human erythrocytes exposed to oxidative stress induced by hyperosmotic sucrose. Methods: Human erythrocytes were treated with sucrose (350–550 mM) to induce oxidative stress and then exposed to Mineral Pitch at concentrations of 0.5, 1.0, and 1.5 g/10 mL. Hemolysis percentage, antioxidant enzyme activities (SOD, GPx, and CAT), mean corpuscular volume (MCV), and calcium channel involvement were analyzed using standard biochemical assays and ELISA. Results: Sucrose elevated hemolysis from 0.16% to 0.24%, while Mineral Pitch significantly reduced it to 0.16% at 1.5 g/10 mL. GPx activity, which decreased to 213.8 U/gHb under stress, was restored to 335 U/gHb. SOD activity improved from 877 U/gHb to 794 U/gHb, and CAT activity increased from 34.6 U/gHb to 44 U/gHb following treatment. MCV dropped to 68 fL with sucrose but was preserved at 85 fL with Mineral Pitch. Furthermore, the use of amlodipine confirmed a calcium-dependent mechanism in eryptosis, modulated by Mineral Pitch. Conclusion: Mineral Pitch demonstrates potent antioxidant and cytoprotective effects on erythrocytes under oxidative stress. It stabilizes cell membranes, restores antioxidant defenses, and regulates calcium-mediated eryptosis. These findings suggest its potential as a natural therapeutic agent against oxidative hematological damage.